2012
DOI: 10.1016/j.cmet.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Tyk2 and Stat3 Regulate Brown Adipose Tissue Differentiation and Obesity

Abstract: Mice lacking the Jak tyrosine kinase member Tyk2 become progressively obese due to aberrant development of Myf5+ brown adipose tissue (BAT). Tyk2 RNA levels in BAT and skeletal muscle, which shares a common progenitor with BAT, are dramatically decreased in mice placed on a high fat diet and in obese humans. Expression of Tyk2 or the constitutively active form of the transcription factor Stat3 (CAStat3) restores differentiation in Tyk2−/− brown preadipocytes. Furthermore, Tyk2−/− mice expressing CAStat3 transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 42 publications
(46 reference statements)
4
77
1
Order By: Relevance
“…It has been previously shown that mice on a high-fat diet present decreased TYK2 expression in brown adipose tissue and skeletal muscle, but not in white adipose tissue and liver, suggesting that modulation of TYK2 expression by diet is tissue specific (38). We did not observe, however, changes in TYK2 expression after exposure of dispersed human islets and EndoC-bH1 human b-cells to high glucose.…”
Section: Discussioncontrasting
confidence: 51%
“…It has been previously shown that mice on a high-fat diet present decreased TYK2 expression in brown adipose tissue and skeletal muscle, but not in white adipose tissue and liver, suggesting that modulation of TYK2 expression by diet is tissue specific (38). We did not observe, however, changes in TYK2 expression after exposure of dispersed human islets and EndoC-bH1 human b-cells to high glucose.…”
Section: Discussioncontrasting
confidence: 51%
“…In line with the disruption of upstream signal transduction, phosphorylation of both STAT3 and STAT5 is significantly attenuated in Jak2-deficient BAT. While the exact role of STAT5 in BAT remains to be elucidated, STAT3 has recently been implicated in BAT differentiation by binding to and enhancing protein stability of PR domain-containing protein 16, a master regulator of brown and beige adipocyte differentiation [14]. Interestingly, in tissue-specific models of Jak2 disruption, STAT3 phosphorylation is reported to be upregulated [28], probably by other protein tyrosine kinases such as members of the Src family [42].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, emerging evidence has linked JAK-STAT signalling to brown and beige adipocyte biology [14][15][16]. Nevertheless, the specific role of JAK2 (a ubiquitously expressed JAK family member) in these processes has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The severe Jak/Stat3 mouse knockout phenotypes, along with their cooperative functions and the lack of genetic tools specifically targeting adipocyte progenitors, has so far limited functional analysis in this cell type. Derecka et al (46) have shown a requirement for Tyk2 in classical brown adipocyte differentiation. However, we observed that in white fat progenitors, Jak1/2, but not Tyk2, seem to be crucial for Stat3 activation ( fig.…”
Section: Discussionmentioning
confidence: 99%